2016
DOI: 10.1089/ten.tec.2015.0501
|View full text |Cite
|
Sign up to set email alerts
|

Man as a Living Bioreactor: Prefabrication of a Custom Vascularized Bone Graft in the Gastrocolic Omentum

Abstract: Reconstruction of critical-size jaw defects still remains challenging. The standard treatment today is transplantation of autologous bone grafts, which is associated with high donor-site morbidity and unsatisfactory outcomes. We aimed to reconstruct a mandibular discontinuity defect after ablative surgery using the gastrocolic omentum as a bioreactor for heterotopic ossification. Three-dimensional computed tomography data were used to produce an ideal virtual replacement for the mandibular defect. A titanium m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
47
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 50 publications
(48 citation statements)
references
References 31 publications
1
47
0
Order By: Relevance
“…Heatmap representing the proportion of publications by year that utilized specific translational research methodologies from construct characterization to human trial to investigate craniofacial tissue engineering 49‐72,74‐77,79,81‐84,145‐197 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Heatmap representing the proportion of publications by year that utilized specific translational research methodologies from construct characterization to human trial to investigate craniofacial tissue engineering 49‐72,74‐77,79,81‐84,145‐197 …”
Section: Discussionmentioning
confidence: 99%
“…The vascularization and precursor cells present in these bioreactors allow for larger bone constructs to be engineered 81 . The first human case of mandibular reconstruction using the greater omentum as a bioreactor was reported in 2016 82 . A follow‐up investigation after 10 months showed that the amount of vital mineralized bone tissue of the graft in the mandible had continued to increase 81 .…”
Section: Discussionmentioning
confidence: 99%
“…This in vivo bioreactor system with ES benefits from one-staged direct application compared to a two-staged procedure where first the bioreactor is transplanted to the well-vascularized heterotopic sites prefabricated, and then, the regenerated tissue is transplanted to the orthotopic site [17,57].…”
Section: Discussionmentioning
confidence: 99%
“…In a groundbreaking study, Wiltfang et al [52] have reconstructed a mandibular discontinuity defect after ablative surgery using the gastrocolic omentum as a bioreactor for heterotopic ossification via a titanium mesh cage filled with bone mineral blocks, infiltrated with 12 mg of recombinant human BMP2, and enriched with bone marrow aspirate. The scaffold was implanted into the gastrocolic omentum, and 3 months later, a free flap was harvested to reconstruct the mandibular defect.…”
Section: Mesenchymal Stem Cells In the Reconstruction Of The Osseous mentioning
confidence: 99%